Specific steps to improve the fairness and sustainability of Medicaid's financing of long-term services and supports for older Americans - Mark J. Warshawsky (American Enterprise Institute (AEI), 2022)
In a prior article (Warshawsky and Marchand, 2017), a colleague and I put forward some broad proposals to improve the system of financing long-term services and supports (LTSS) for older Americans, to make it fairer, more sustainable, and more consistent with the value of self-reliance. In this report, I update the basis for those proposals and make them more specific, so that legislation could be written to implement them. Based on newly available unpublished data, I calculate a new lower bound estimate of how much additional resources would be available to states and the federal government from more effective enforcement of the estate recovery rules in Medicaid for LTSS — 3 billion instead of the current 700 million collected nationally. This estimate is based on the superior but not remarkable efforts of a few states, compared to the mediocre activity of many states and the nearly non-existent efforts of a few. I also explain how the state Medicaid LTSS eligibility and recovery rules could be better designed and administered, in particular by including retirement accounts as countable assets and outlawing various transfer techniques used by the well-to-do to qualify. These recommendations are in strong contrast to those contained in a recent report from the Medicaid and CHIP Payment and Access Commission (MACPAC), which recommended that estate recovery should be made optional for states and passed on addressing other fairness issues. In light of the falling birth rate in the US, which will increase the demand for paid LTSS care in the future even beyond the aging of the baby boom generation already increasing the Medicaid funding burden on governments, and the continued failure of California to follow federal Medicaid laws and its proposal to waive all asset tests, the reforms I recommend here for federal Medicaid matching to encourage state efforts and changes and to encourage individuals' insurance and asset accumulation are essential.
Keywords: A; 330; Aging; Health Care Policy; Medicaid; Medicaid-CHIP; State And Local Budgets; US Deficit